Market Segmentation Analysis of Central Sulawesi’s Processed Chocolate Product at Palu City - Muhammad Rizal Faiz; Wildani Pingkan H; Yulianti Kalaba (AGROLAND The Agricultural Sciences Journal (e-Journal), 2015)
By observing the development of cacao as one of the Central Sulawesi’s best commodity that widely processed as chocolate, thus studywas conducted withobjective to give the information about Central Sulawesi’s processed chocolate product market segments. Location determination is conducted deliberately, with the amount of respondent of 102 people that proportionally distributed among 5 districts, which is 21 people at Palu Barat District, 24 people at PaluTimur District, 21 people at Palu Selatan Disctric, 14 people at Tatanga District and 22 people at Mantikulore District that determined using Proportional Stratified Random Sampling method. It is done with the consideration that the respondents can represent Palu City’s residents. Analysis that wasused in this studyisTwoStep Cluster analysis for market segment determination. Result from this study showed that Palu City’s resident splittedinto 3 segments, which is segment 1 as the largest segment but has low processed chocolate consumption, segment 2 as the smallest segment with moderate consumption and expenses for processed chocolate products and segment 3 as the second largest segment which is the most potential segment because of their high consumption and expenses for processed chocolate products.